(untitled) (Al-Aasar, 2025)
This abstract examines the key aspects of next-generation sustainable packaging and safety within the rapidly expanding halal food industry. With a growing Muslim population worldwide, there’s an increased demand for products that are not only halal-compliant but also environmentally friendly. This study sheds light on the dual challenges of ensuring packaging materials and methods align with strict Islamic dietary laws (Sharia) while simultaneously adopting eco-friendly solutions. Key areas of focus include: • The research investigates how modern packaging designs and materials prevent contact with haram (forbidden) substances, such as animal-derived gelatin in adhesives or non-halal lubricants. • The paper analyzes the use of biodegradable, compostable, and recycled materials, such as plant-based polymers and sugarcane pulp, to reduce the industry’s environmental impact. • It delves into how smart packaging with sensors, QR codes, and blockchain technology improves traceability by verifying the halal status of products from farm to table and building consumer trust. The abstract concludes that incorporating these next-generation packaging solutions is essential for the halal food industry to meet consumers’ rising expectations for both religious adherence and ethical consumption. The findings underscore the need for standardized global regulations and collaborative research to overcome current cost and scalability barriers.